High levels of infectiousness of asymptomatic Leishmania (Viannia) braziliensis infections in wild rodents highlights their importance in the epidemiology of American Tegumentary Leishmaniasis in Brazil. - José Ferreira Marinho-Júnior; Juliana F C L S Monteiro; Ana Waléria Sales de Carvalho; Francisco Gomes de Carvalho; Milena de Paiva Cavalcanti; Jeffrey Shaw; Orin Courtenay; Sinval Pinto Brandão-Filho (Public Library of Science (PLoS), 2023)
Background The epidemiological significance of wildlife infections with aetiological agents causing human infectious diseases is largely determined by their infection status, contact potential with humans (via vectors for vector-borne diseases), and their infectiousness to maintain onward transmission. This study quantified these parameters in wild and synanthropic naturally infected rodent populations in an endemic region of tegumentary leishmaniasis in northeast Brazil. Methods Capture-mark-recapture (CMR) of rodents was conducted over 27 months in domestic/peri domestic environs, household plantations and nearby Atlantic Forest (9,920 single trap nights). Rodent clinical samples (blood and ear tissue) were tested for infection by conventional PCR and quantitative PCR (qPCR) for Leishmania (Viannia) braziliensis, and xenodiagnosis to measure infectiousness to the local sand fly vector. Results A total 603 individuals of 8 rodent species were (re)captured on 1,051 occasions. The most abundant species were Nectomys squamipes (245 individuals, 41% of the total catch), Rattus rattus (148, 25%), and Necromys lasiurus (83, 14%). All species were captured in greater relative frequencies in plantations; R. rattus was the only species captured in all three habitats including in and around houses. Four species, comprising 22.6% of individuals captured at least twice, were geolocated in more than one habitat type; 78.6% were infected with L. (V.) braziliensis, facilitating inter-species and inter-habitat transmission. Species specific period prevalence ranged between 0%-62% being significantly higher in N. squamipes (54-62%) and Hollochillus sciureus (43-47%). Xenodiagnosis was performed on 41 occasions exposing 1,879 Nyssomyia whitmani sand flies to five rodent species (37 individuals). Similar mean levels of infectiousness amongst the more common rodent species were observed. Longitudinal xenodiagnosis of the N. squamipes population revealed a persistent level of infectiousness over 13 months follow-up, infecting a median 48% (IQR: 30.1%-64.2%) of exposed blood-fed vectors. The proportion of exposed flies infected was greater in the low compared to in the high seasonal period of vector abundance. L. (V.) braziliensis parasite loads in rodent blood quantified by qPCR were similar across rodent species but did not represent a reliable quantitative marker of infectiousness to sand flies. The standardised risk of rodent infection in plantations was 70.3% relative to 11.3% and 18.4% in peri domestic and forest habitats respectively. R. rattus was the only exception to this trend indicating greatest risk in the peri domestic environment. Conclusions The results support the view that a collective assemblage of wild and synanthropic rodent species is an important wild reservoir of L. (V.) braziliensis in this region, with N. squamipes and R. rattus probably playing a key role in transmission within and between habitat types and rodent species. Rodents, and by implication humans, are at risk of infection in all sampled habitats, but more so in homestead plantations. These conclusions are based on one of the longest CMR study of small rodents in an American Tegumentary Leishmaniasis (ATL) foci.